Data‐driven simulation of metastatic processes within brain tissue. Issue 1 (15th March 2018) - Schröder, Patrick; Wagner, Arndt; Stöhr, Daniela; Rehm, Markus; Ehlers, Wolfgang
Abstract: The modelling of biological processes like the metastasation of lung cancer in brain tissue requires the inclusion of the major processes at the metastasis site as well as to identify model parameters from experiments. In this regard, experimental data from proliferation, malnutrition and drug experiments are embedded into a continuum‐mechanical metastases model. Successfully implemented, such models can serve as prototype tools to estimate the metastases growth and response to therapeutic applications. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)